Pengembangan Media Ular Tangga Bilangan Bulat pada Pelajaran Matematika di Sekolah Dasar - Defa, Defa (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to determine the feasibility and effectiveness of the Integer Snakes and Ladders media in mathematics lessons on integer calculation material in grade VI elementary school. The subjects of this study were students of class VI Elementary School 11 Rantau Selatan totaling 30 people. This research uses Research and Development (R&D) research. Data validation was carried out by material experts and media experts, as well as by comparing student learning outcomes before and after using Integers Snakes and Ladders Media. The value of the media expert validation results at stage 1 was 70% with the "Good" category, while in stage II it was 90% with the "Very Good" category. The results of the validation of material experts in stage 1 were 72% in the "Good" category, while in stage II it was 88% in the "Very Good" category. The average student learning outcomes before using the media was 54.33%, after the trial of using the snake and ladder integer learning media in stage 1 it was 70%, and in stage II it was 82.66%. It can be concluded that the learning media for snakes and ladders integers is feasible and effective to use in learning integers in grade VI elementary school.